Endocannabinoids and Schizophrenia - Stéphane Potvin; Lahcen Ait Bentaleb; Emmanuel Stip; Joëlle Desfosss (MDPI AG, 2010)
The endocannabinoids anandamide and 2-arachydonoylglycerol (2-AG) are lipids naturally derived from membrane precursors which bind cannabinoid receptors (CB1, CB2). This endocannabinoid system is disturbed in schizophrenia. Indeed, there seems to be an association between schizophrenia and polymorphisms of the CB1 receptor gene. Moreover, CB1 receptors are found in higher density in the prefrontal cortex, hippocampus and basal ganglia of patients with schizophrenia. Similarly, anandamide levels are increased in the cerebrospinal fluid (CSF) and in the serum of schizophrenia patients, including during the prodromal state, suggesting that they may play a protective role in psychosis homeostasis. Future studies are needed to further explore the role of the endocannabinoid system in the pathophysiology of schizophrenia.